HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN TINGKAT KONTROL ASMA PASIEN ASMA DI RS SYAFIRA KOTA PEKANBARU - Octariany Octariany (Collaborative Medical Journal, 2023)
Asthma is a public health problem in almost all countries, experienced by children to adults with mild to severe stages, and can result in death. In general, good asthma control results in a reduced risk of asthma exacerbations. The level of asthma control is divided into three parts, namely fully controlled, partially controlled and not controlled. Based on the Body Mass Index (BMI) people who are overweight are 6 times more likely to have uncontrolled asthma than people who have normal weight. Data analysis in this study will use the Pearson correlation test with a sample size of 35 people. To determine the relationship between body mass index and asthma control level of asthma patients at syafira hospital pekanbaru city. As many as 94% of study subjects had uncontrolled asthma and 6% had partially controlled asthma and none of the study subjects had fully controlled asthma. There is no significant relationship between body mass index and asthma control level (p=0.194). There was no association between body mass index with asthma control level on asthmatic patient at Syafira hospital Pekanbaru city.